Microplastic ingestion by zooplankton in surf zone waters of sandy beaches: Are copepods potential reservoirs of these emerging pollutants? - Corradini, Rosario (2025)
This study investigates the ingestion of microplastics (MPs) by zooplankton in the surf zone of southwestern Atlantic sandy beaches, an extremely turbulent environment with high interaction between suspended particles. Sampling was conducted on November 22 and June 23 to assess the presence of MPs in the surf zone water column and dominant zooplankton (Acartia tonsa, Paracalanus parvus, Euterpina acutifrons) and to analyze ingestion patterns across species and beaches. Results showed MP concentrations in seawater ranging from 400 to 1750 items m− 3 , with fibers accounting for 92 %, predominantly in transparent, blue, and black. Ingested MPs ranged from 0.07 to 0.24 items individual− 1 , based on the analysis of 350 individuals of A. tonsa, 500 of P. parvus, and 500 of E. acutifrons. Fibers made up 74 % of ingested particles. Chlorinated polyethylene dominated seawater and polypropylene zooplankton. Different tendencies in species-specific MP ingestion were observed, with A. tonsa consuming a wider variety of MP types and sizes than P. parvus and E. acutifrons. Fibers were the most common type of ingested MPs, followed by fragments and films. Ingestion rates were low, but copepods retained from 7.2 to 1048.1 items m− 3 , demonstrating their high potential as reservoirs of MPs. This study provides evidence of MP ingestion by zooplankton in surf zones, highlighting their role as entry points within coastal food webs. Additionally, it highlights the importance of understanding species-specific responses to MP exposure, which is crucial for accurately assessing the ecological risks associated with plastic pollution in coastal marine environments.